PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Pawestri, Adelina Surya Hati Pawestri (Jurnal PGSD Indonesia, 2025)
This study aimed to explore the development of digital media in enhancing reading literacy among elementary school students. The study employed a qualitative method using a library research approach. Data were obtained from various academic books, journal articles, and research reports related to reading literacy and digital media in education. The analysis was conducted through content analysis and qualitative interpretation. The research findings indicated that the integration of digital media, such as interactive digital books, mobile literacy applications, educational videos, educational games, literacy blogs, and digital comics, contributed significantly to improving students' reading motivation, engagement, and comprehension. Digital media provided diverse and meaningful reading experiences that aligned with the principles of active literacy and multimedia learning. Moreover, digital media facilitated social interaction and scaffolding, which supported the development of cognitive and social competencies. The study concluded that strategically designed digital media could enhance the quality of reading literacy in elementary education. The implications suggested the need for teachers to improve their digital media design skills and for developers to create adaptive and pedagogically sound educational products. Future research was recommended to examine the contextual effectiveness of various digital media models in supporting comprehensive literacy outcomes.